2021
DOI: 10.2174/1385272825666210812102815
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Activity of 2,7-Naphthyridine Derivatives: An Overview

Abstract: : 2,7-Naphthyridine is one of the six structural isomers of pyridopyridine. Biological investigations have shown that these compounds have a broad spectrum of activity. They have been found to have antitumor, antimicrobial, analgesic and anticonvulsant effects. The broad spectrum of biological activity of 2,7-naphthyridine derivatives is the main reason for the preparation of new compounds containing this scaffold. This review aims to present various methods of obtaining 2,7-naphthyridine analogs. Compounds co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…In an our previous work, 20 we synthesized pyrazolo [3,4c]tetrazolo [5,1-a]-2,7-naphthyridine 8, and it was found that in the solid state and in solution, it existed exclusively in the tetrazole form. As expected, heating compound 1 with hydrazine hydrate in ethanol at reflux afforded the corresponding 10-benzyl-8,9,10,11-tetrahydro-5H-pyrazolo [3,4-c][1,2,4]triazolo [3,4-a]-2,7naphthyridin-7-amine (7). Compounds 7 and 8 were then heated at reflux (5 h) with acetylacetone to obtain the 5-benzyl-9,11-dimethyl-4,5,6,7-tetrahydropyrimido[1',2': (10), respectively, via the well known Knorr synthesis of pyrazoles (Scheme 3).…”
Section: Resultssupporting
confidence: 69%
See 3 more Smart Citations
“…In an our previous work, 20 we synthesized pyrazolo [3,4c]tetrazolo [5,1-a]-2,7-naphthyridine 8, and it was found that in the solid state and in solution, it existed exclusively in the tetrazole form. As expected, heating compound 1 with hydrazine hydrate in ethanol at reflux afforded the corresponding 10-benzyl-8,9,10,11-tetrahydro-5H-pyrazolo [3,4-c][1,2,4]triazolo [3,4-a]-2,7naphthyridin-7-amine (7). Compounds 7 and 8 were then heated at reflux (5 h) with acetylacetone to obtain the 5-benzyl-9,11-dimethyl-4,5,6,7-tetrahydropyrimido[1',2': (10), respectively, via the well known Knorr synthesis of pyrazoles (Scheme 3).…”
Section: Resultssupporting
confidence: 69%
“…9-Benzyl-5-chloro-7,8,9,10-tatrahydro [1,2,4]triazolo [3,4-a]-2,7-naphthyridin-6-carbonitrile (1) 24 was used as starting compound for the synthesis. Its reaction with ethyl mercaptoacetate led to the cyclization of a thiophene ring with formation of ethyl 7-amino-10-benzyl-8,9,10,11-tetrahydrothieno[2,3c] [1,2,4]triazolo [3,4-a]-2,7-naphthyridin-6-carboxylate (2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2,7-Naphthyridine derivatives are interesting compounds in the field of heterocyclic chemistry due to some of their interesting biological activities, as evidenced by recent reviews [ 1 , 2 , 3 ]. Literature data shows that some 2,7-naphthyridine derivatives are potent and selective 3-phosphoinositide-dependent Kinase-1 [ 4 ], PDE5 [ 5 ], c-Kit/VEGFR-2 Kinase [ 6 ] inhibitors, while pyrazolo[3,4- c ]-2,7-naphthyridines are bombesin receptor subtype-(3BRS-3) agonists [ 7 ].…”
Section: Introductionmentioning
confidence: 99%